Let N be equal to the following integral. What is ⌊ N ⌋ ? ∫ 0 2 e x ( x 3 + 3 x 2 + 4 x + 4 ) d x
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let g ( x ) = e x f ( x )
Hence g ′ ( x ) = e x ( f ( x ) + f ′ ( x ) )
Now in our case f ( x ) = x 3 + 4 x
Hence ∫ 0 2 e x ( x 3 + 3 x 2 + 4 x + 4 ) d x = ( e x ( x 3 + 4 x ) ) ∣ 0 2 = 1 6 e 2
Problem Loading...
Note Loading...
Set Loading...
This integral can be done by parts, but I didn't call it "sneaky" for nothing!
Take a look at the polynomial: x 3 + 3 x 2 + 4 x + 4 . Rearrange it so it is x 3 + 4 x + 3 x 2 + 4 and let u = x 3 + 4 x . Note that u ′ = 3 x 2 + 4 . Adding u and u ′ gives the original polynomial, so we can say this. ∫ 0 2 e x ( x 3 + 3 x 2 + 4 x + 4 ) d x = ∫ 0 2 e x ( u + u ′ ) d x Let's see if there is an easy way to find the antiderivative of e x ( u + u ′ ) . Let v = e x . Note that v ′ = e x . We are now trying to find the antiderivative of u v + u ′ v . Knowing that v = v ′ , we can say we are trying to find the antiderivative of u v ′ + u ′ v . This, by the Product Rule, is equal to ( u v ) ′ . Substituting u and v back in, we can say this. ∫ e x ( x 3 + 3 x 2 + 4 x + 4 ) d x = e x ( x 3 + 4 x ) + C All we need to now is plug in 0 and 2 . e x ( x 3 + 4 x ) ] 0 2 = e 2 ( 8 + 8 ) − e 0 ( 0 + 0 ) = 1 6 e 2 N = 1 6 e 2 ≈ 1 1 8 . 2 2 4 8 9 … , so ⌊ N ⌋ = 1 1 8